Improving Quality of Educational Institutions through Teacher Performance Evaluation with Perspective of CIPP Theory. - Imam Syafi'i; Yahya Aziz; KHIFDLIYAH, AFRIDATUL; Acmad Isa Al Firdausi; Rossanda Nur Afianty (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
The enhancement of educational institution standards has emerged as a primary concern in the field of education, with the effectiveness of teachers being a crucial element in achieving successful learning outcomes. This study intends to assess teacher effectiveness through the lens of the CIPP (Context, Input, Process, Product) model to elevate educational quality. A qualitative approach using a case study methodology has been utilized for this investigation. Participants involved in this research consist of educators and administrative staff from schools. Data collection methods included observation, interviews, and documentation analysis, while the data processing was guided by the interactive model created by Miles and Huberman. The findings of this research show that context evaluation uncovers various obstacles within the educational setting, particularly issues around discipline and the preparedness of teachers to instruct effectively. Input evaluation stresses the necessity of ongoing professional development to improve both the pedagogical skills and professional abilities of teachers. Process evaluation indicates that creative teaching approaches and effective classroom management are integral to enhancing learning quality. Product evaluation suggests that well-organized assessments of teacher performance have a favorable influence on the overall educational quality. The recommendations arising from this research underscore the importance of establishing more robust institutional policies to foster teacher development, the regular updating of the CIPP evaluation framework, and the need for intensified training tailored to contemporary educational demands.